Orchestration of protein acetylation as a toggle for cellular defense and virus replication. Issue 1 (December 2018) - Murray, L.; Sheng, X.; Cristea, I.
Abstract Emerging evidence highlights protein acetylation, a prevalent lysine posttranslational modification, as a regulatory mechanism and promising therapeutic target in human viral infections. However, how infections dynamically alter global cellular acetylation or whether viral proteins are acetylated remains virtually unexplored. Here, we establish acetylation as a highly-regulated molecular toggle of protein function integral to the herpesvirus human cytomegalovirus (HCMV) replication. We offer temporal resolution of cellular and viral acetylations. By interrogating dynamic protein acetylation with both protein abundance and subcellular localization, we discover finely tuned spatial acetylations across infection time. We determine that lamin acetylation at the nuclear periphery protects against virus production by inhibiting capsid nuclear egress. Further studies within infectious viral particles identify numerous acetylations, including on the viral transcriptional activator pUL26, which we show represses virus production. Altogether, this study provides specific insights into functions of cellular and viral protein acetylations and a valuable resource of dynamic acetylation events. The dynamics of protein acetylation during infection remains unexplored. Here, Murray et al. characterize spatio-temporal acetylations of both cellular and viral proteins during HCMV infection, providing new functional insights into the host-virus acetylome that might help identify new antiviral targets.